Optimizing Medical Services through AGI Policies to Enhance Provider Network Performance - Bordas, Maria (Journal of Global Economy, Business and Finance, 2025)
The U.S. healthcare system faces critical provider shortages and administrative inefficiencies, especially in underserved areas. This paper explores the transformative potential of Artificial General Intelligence [1] (AGI) to optimize healthcare provider network performance. By leveraging AGI's capabilities in predictive analytics, healthcare systems can anticipate patient needs and implement proactive care strategies. AGI can automate administrative tasks, streamline operations, reduce costs, and allow providers to focus more on patient care. Enhanced decision support from AGI can improve diagnostic accuracy and efficiency. This review proposes a framework for integrating AGI into healthcare, emphasizing its potential to improve access to quality care and enhance patient outcomes.